Oral Delivery of Prolyl Hydroxylase Inhibitor: AKB-4924 Promotes Localized Mucosal Healing in a Mouse Model of Colitis. Issue 2 (February 2015) - Marks, Ellen; Goggins, Bridie J.; Cardona, Jocelle; Cole, Siobhan; Minahan, Kyra; Mateer, Sean; Walker, Marjorie M.; Shalwitz, Robert; Keely, Simon
Abstract : Background: Pharmacological induction of hypoxia-inducible factor (HIF), a global transcriptional regulator of the hypoxic response, by prolyl hydroxylase inhibitors (PHDi) is protective in murine models of colitis, and epithelial cells are critical for the observed therapeutic efficacy. Because systemic HIF activation may lead to potentially negative off-target effects, we hypothesized that targeting epithelial HIF through oral delivery of PHDi would be sufficient to protect against colitis in a mouse model. Methods: Using a chemically induced trinitrobenzene sulfonic acid murine model of colitis, we compared the efficacy of oral and intraperitoneal (i.p.) delivery of the PHDi; AKB-4924 in preventing colitis, as measured by endoscopy, histology, barrier integrity, and immune profiling. Furthermore, we measured potential off-target effects, examining HIF and HIF target genes in the heart and kidney, as well as erythropoietin and hematocrit levels. Results: Oral administration of AKB-4924 exhibited mucosal protection comparable i.p. dosing. Oral delivery of PHDi led to reduced colonic epithelial HIF stabilization compared with i.p. delivery, but this was still sufficient to induce transcription of downstream HIF targets. Furthermore, oral delivery of PHDi led to reduced stabilization of HIF and activation of HIF targets in extraintestinal organs. Conclusions: Oral delivery of PHDi therapies to this intestinal mucosa protects against colitis in animal models and represents a potential therapeutic strategy for inflammatory bowel disease, which also precludes unwanted extraintestinal effects. Abstract : Article first published online 24 December 2014.